Simulation of congenital heart defects: a novel way of training in echocardiography. Issue 8 (8th January 2009) - Weidenbach, M; Rázek, V; Wild, F; Khambadkone, S; Berlage, T; Janoušek, J; Marek, J
Abstract : Background: Echocardiography is one of the most important diagnostic imaging modalities in paediatric cardiology. Owing to the large number of lesions, achieving expertise often requires years of training. Echocardiography is still taught using the apprenticeship model, which is time- and personnel consuming. Objectives: To extend the echocardiography simulator EchoCom to enable simulation of congenital heart lesions and validate it for training in paediatric echocardiography. Methods: The simulator consists of a life-size manikin, a dummy transducer with attached three-dimensional (3D) tracking system and a computer application. Transthoracic real-time (RT) 3D echocardiographic datasets were collected and embedded into the simulator. Two-dimensional images were calculated and resliced from these datasets according to the position of the tracking sensor. Ten RT 3D datasets of congenital heart lesions were selected for validation. Datasets were blinded and without additional information presented to 43 participants who were stratified according to their expertise (12 experts, 16 intermediates, 15 beginners). Participants were asked to list the relevant findings and make a diagnosis. Construct validation was tested comparing diagnostic performance for each group. Face and content validation were tested using a standardised questionnaire. Results: Participants judged the simulator as realistic and useful. The main drawback was the adult size of the manikin. The diagnostic performance of each group differed significantly proving construct validity. Conclusions: According to this validation the prototype simulator could make a significant contribution to training in the use of echocardiography in congenital heart disease.